2015
DOI: 10.1177/0003319715574625
|View full text |Cite
|
Sign up to set email alerts
|

Increased Platelet to Lymphocyte Ratio is Related to Slow Coronary Flow

Abstract: Previous studies showed that both inflammation and platelets have a role in development of slow coronary flow (SCF). Platelet to lymphocyte ratio (PLR) as an emerging inflammatory indicator was significantly associated with adverse cardiovascular events. Therefore, we aimed to assess the relationship between PLR and SCF. Patients who had angiographically normal coronary arteries were enrolled in this retrospective study (n ¼ 221 as SCF group and n ¼ 293 as control group). Patients who had thrombolysis in myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
0
34
3
1
Order By: Relevance
“…However, the literature that was reviewed included no data about the association between PLR and the severity of degenerative AVS in patients with normal systolic function. [23456789] Degenerative AVS and aortic annular calcification have a close relationship with atherosclerotic changes in various vascular systems of the human body such as CAD and carotid atherosclerosis. [1011] Although the precise underlying pathophysiology of degenerative AVS still remains unclear, metabolic imbalances, particularly those including calcium and phosphorus accumulation, play a role as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature that was reviewed included no data about the association between PLR and the severity of degenerative AVS in patients with normal systolic function. [23456789] Degenerative AVS and aortic annular calcification have a close relationship with atherosclerotic changes in various vascular systems of the human body such as CAD and carotid atherosclerosis. [1011] Although the precise underlying pathophysiology of degenerative AVS still remains unclear, metabolic imbalances, particularly those including calcium and phosphorus accumulation, play a role as well.…”
Section: Discussionmentioning
confidence: 99%
“…Because PLR is a ratio, it is relatively more stable than individual blood parameters, which may be altered by several variables (e.g., dehydration, overhydration, and blood specimen handling) [31]. The advantage of PLR calculation could be that it reflects the condition of both aggregation and inflammatory pathways and it may be more valuable than either platelet or lymphocyte count alone in the prediction of various inflammatory diseases including cardiovascular diseases [19,32]. In a previous study, Azab et al [33] showed that lower lymphocyte and higher platelet counts were significantly related to worse prognosis in patients with non-ST-elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies, total white blood cell count has not been the predictor of CSFP 6,1315. In contrast, Akboga et al16 found that a higher white blood cell count is associated with CSFP. Regarding the red blood cell subtypes, results have also been diverse among studies.…”
mentioning
confidence: 95%
“…Furthermore, the elevated levels of hemoglobin11 and hematocrit15 have been associated with the CSFP. In addition to these regular complete blood cell count components, some novel biomarkers have also been found to be associated with the CSFP, including elevated neutrophil-to-lymphocyte ratio,14 increased platelet-to-lymphocyte ratio,16 and decreased lymphocyte-to-monocyte ratio 18. All these novel biomarkers are inflammation-based and have been useful in diagnosing other inflammatory diseases.…”
mentioning
confidence: 99%